Decreasing Electron Flux through the Cytochrome and/or Alternative Respiratory Pathways Triggers Common and Distinct Cellular Responses Dependent on Growth Conditions . Issue 1 (6th November 2014) - Kühn, Kristina; Yin, Guangkun; Duncan, Owen; Law, Simon R.; Kubiszewski-Jakubiak, Szymon; Kaur, Parwinder; Meyer, Etienne; Wang, Yan; Small, Catherine Colas des Francs; Giraud, Estelle; Narsai, Reena; Whelan, James
Abstract : Diverse signaling pathways are activated by perturbation of mitochondrial function under different growth conditions . Abstract: Diverse signaling pathways are activated by perturbation of mitochondrial function under different growth conditions.Mitochondria have emerged as an important organelle for sensing and coping with stress in addition to being the sites of important metabolic pathways. Here, responses to moderate light and drought stress were examined in different Arabidopsis ( Arabidopsis thaliana ) mutant plants lacking a functional alternative oxidase ( alternative oxidase1a [ aox1a ]), those with reduced cytochrome electron transport chain capacity ( T3/T7 bacteriophage-type RNA polymerase, mitochondrial, and plastidial [ rpoTmp ]), and double mutants impaired in both pathways ( aox1a : rpoTmp ). Under conditions considered optimal for growth, transcriptomes of aox1a and rpoTmp were distinct. Under adverse growth conditions, however, transcriptome changes in aox1a and rpoTmp displayed a highly significant overlap and were indicative of a common mitochondrial stress response and down-regulation of photosynthesis. This suggests that the role of mitochondria to support photosynthesis is provided through either the alternative pathway or the cytochrome pathway, and when either pathway is inhibited, such as under environmental stress, a common, dramatic, and succinct mitochondrial signal is activated to alter energy metabolism in both organelles. aox1a : rpoTmp double mutants grown under optimal conditions showed dramatic reductions in biomass production compared with aox1a and rpoTmp and a transcriptome that was distinct from aox1a or rpoTmp . Transcript data indicating activation of mitochondrial biogenesis in aox1a : rpoTmp were supported by a proteomic analysis of over 200 proteins. Under optimal conditions, aox1a : rpoTmp plants seemed to switch on many of the typical mitochondrial stress regulators. Under adverse conditions, aox1a : rpoTmp turned off these responses and displayed a biotic stress response. Taken together, these results highlight the diverse signaling pathways activated by the perturbation of mitochondrial function under different growth conditions.